Membrane Vesicles of Pectobacterium as an Effective Protein Secretion System - Joanna Jonca (MDPI AG, 2021)
Bacteria of genus Pectobacterium are Gram-negative rods of the family Pectobacteriaceae. They are the causative agent of soft rot diseases of crops and ornamental plants. However, their virulence mechanisms are not yet fully elucidated. Membrane vesicles (MVs) are universally released by bacteria and are believed to play an important role in the pathogenicity and survival of bacteria in the environment. Our study investigates the role of MVs in the virulence of Pectobacterium. The results indicate that the morphology and MVs production depend on growth medium composition. In polygalacturonic acid (PGA) supplemented media, Pectobacterium produces large MVs (100–300 nm) and small vesicles below 100 nm. Proteomic analyses revealed the presence of pectate degrading enzymes in the MVs. The pectate plate test and enzymatic assay proved that those enzymes are active and able to degrade pectates. What is more, the pathogenicity test indicated that the MVs derived from Pectobacterium were able to induce maceration of Zantedeschia sp. leaves. We also show that the MVs of β-lactamase producing strains were able to suppress ampicillin activity and permit the growth of susceptible bacteria. Those findings indicate that the MVs of Pectobacterium play an important role in host-pathogen interactions and niche competition with other bacteria. Our research also sheds some light on the mechanism of MVs production. We demonstrate that the MVs production in Pectobacterium strains, which overexpress a green fluorescence protein (GFP), is higher than in wild-type strains. Moreover, proteomic analysis revealed that the GFP was present in the MVs. Therefore, it is possible that protein sequestration into MVs might not be strictly limited to periplasmic proteins. Our research highlights the importance of MVs production as a mechanism of cargo delivery in Pectobacterium and an effective secretion system.